Is Self-Regulated Peer Review Effective at Signaling Audit Quality? - Casterella, Jeffrey R.; Jensen, Kevan L.; Knechel, W. Robert (The Accounting Review, 2009)
ABSTRACT: This study examines whether peer reviews conducted under the AICPA's self-regulatory model have been effective at signaling audit quality. Prior research has examined whether peer-review reports are associated with perceived audit quality. We examine whether peer-review reports are associated with actual audit quality. Using a unique data set obtained from the files of an insurance company, we find that peer-review findings are indeed useful in predicting audit failure (i.e., malpractice claims alleging auditor negligence), and that certain types of findings are particularly useful in this regard. We also find that peer-review findings are associated with other firm-specific indicators of potentially weak quality control or risky practices within accounting firms. Taken together, we interpret our findings to indicate that self-regulated peer review as mandated by the AICPA does provide effective signals regarding audit-firm quality.